2017
DOI: 10.1590/1678-4766e2017154
|View full text |Cite
|
Sign up to set email alerts
|

Checklist das aves do Estado do Mato Grosso do Sul, Brasil

Abstract: ABSTRACT. Checklist of the birds of the state of Mato Grosso do Sul, Brazil. Contrasting with several other Brazilian states, just recently the state of Mato Grosso do Sul started to organize an inventory of its birdlife. We list 630 species of birds for the Mato Grosso do Sul, belonging to 26 orders and 74 families, representing 34% of birds occurring in Brazil. About 90% of these species have documented records of its occurrence in the state (Main List), according to proposed by CBRO. The others species stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
(11 reference statements)
1
9
0
9
Order By: Relevance
“…Richness and abundance. The 29 species of reptiles identified here represent 15% of reptile richness (188 species), and the 47 species of birds represent 7% of the avifauna (630 species) previously reported for Mato Grosso do Sul (Ferreira et al 2017, Nunes et al 2017. The richness estimated for road-killed reptiles supports a more complete sample in PAN and CER than in the transitional landscapes of the ECO and URU, where it is likely that several other road-killed species were not recorded.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Richness and abundance. The 29 species of reptiles identified here represent 15% of reptile richness (188 species), and the 47 species of birds represent 7% of the avifauna (630 species) previously reported for Mato Grosso do Sul (Ferreira et al 2017, Nunes et al 2017. The richness estimated for road-killed reptiles supports a more complete sample in PAN and CER than in the transitional landscapes of the ECO and URU, where it is likely that several other road-killed species were not recorded.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, it is notable that 83 Eunectes notaeus and 4 Dracaena paraguayensis were road-killed at reproductive ages (Table 2); such mortality could negatively impact their population sizes. For bird species, the most recent checklist does not classify species occurrences by macroregions in Mato Grosso do Sul (Nunes et al 2017), so we found no first geographical records, but we did record 12 new species of road-killed birds in Brazil. Large aquatic birds like Jabiru mycteria and Aramus guarauna, as well as small ones like Aramides cajaneus, Jacana jacana, and Chloroceryle americana are quite unusual road-killed species.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Além disso, também são observados remanescentes de Mata Atlântica no sul e leste do estado (Godoi et al 2013), manchas de floresta seca, também conhecidas como Florestas Chiquitanas, no extremo noroeste, na divisa com a Bolívia (Godoi & Souza 2016), e de Chaco no extremo oeste, na divisa com o Paraguai (Straube et al 2006). Devido à grande extensão territorial e presença de diferentes domínios biogeográficos, o Mato Grosso do Sul apresenta alta riqueza de espécies de aves, com ao menos 630 espécies pertencentes a 26 ordens e 74 famílias (Nunes et al 2017), o que corresponde a aproximadamente 33% das 1919 espécies de aves do Brasil (Piacentini et al 2015).…”
Section: Introductionunclassified